2020
DOI: 10.1002/fsn3.2061
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in the bioactive proteins in human milk of the Chinese population: A systematic review

Abstract: This systematic review aimed at investigating longitudinal changes in human milk bioactive protein concentrations in Chinese population. Both English and Chinese databases were searched. The data were pooled into six defined lactation stages. Weighted means of protein concentrations in each stage and the statistical significance of means of different lactation stages were calculated. The data of 11 bioactive proteins were retrieved. Concentrations of sIgA, IgM, and IgG decreased sharply during the first 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…2 And it also can enhance the emotional com-munication between mother and infant. Current research on HM composition mainly focuses on HM methodological research, [3][4][5] HM composition and infant health effects, 6,7 intervention on HM composition, 1,8,9 HM dynamic changes influencing factors, [10][11][12] and the secretion mechanism. 13 HM is the first-choice food for babies, and the nutritional components change dynamically according to a variety of influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…2 And it also can enhance the emotional com-munication between mother and infant. Current research on HM composition mainly focuses on HM methodological research, [3][4][5] HM composition and infant health effects, 6,7 intervention on HM composition, 1,8,9 HM dynamic changes influencing factors, [10][11][12] and the secretion mechanism. 13 HM is the first-choice food for babies, and the nutritional components change dynamically according to a variety of influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the Chinese population showed immunoglobulins sharply decreased over lactation, particularly from the early to transitional milk. In contrast, this same study found that the lysozyme increased throughout lactation [23]. The functionality of these changing human milk proteins also vary over lactation.…”
Section: The Uniqueness Of the Preterm Human Milk Proteomementioning
confidence: 64%
“…The WHO defines early breastfeeding as starting breast milk feeding within one hour of delivery (Abie & Goshu, 2019). Breast milk contains a complex nutritional matrix that includes proteins and amino acids, lipids, lactose and oligosaccharides, vitamins, minerals, and other compounds (Ren et al, 2021).…”
Section: Introductionmentioning
confidence: 99%